Intercultural therapy with Ultra-Orthodox Jews in Israel: the complexity of the encounter between secular therapists and Haredi clients - Doron, Einat; Tobis, Sławomir; Domaradzki, Jan (Frontiers in Psychology, 2024)
This paper explores the exceptional intercultural encounter between secular therapists and Ultra-Orthodox Jews in Israel, focusing on two key aspects. Firstly, it explores the distinctive attributes and conflicts inherent in treating Ultra-Orthodox individuals. On the one hand is the secular Israeli therapist, whose base is in Western philosophy that prioritizes individuality, cultural diversity, and tolerance of differences. On the other hand is the Haredi client, entrenched in values from Jewish tradition and religious principles that amplify solidarity and collectivism while rejecting prevalent secular culture. The existing socio-political climate in Israel often positions these two as potentially conflicting cultures. Secondly, the paper seeks to illuminate the uncommon dynamics of the minority-majority power balance within the therapeutic relationship. In contrast to prevalent literature in intercultural therapy, which typically frames the client as a representative of a disadvantaged minority and the therapist as a representative of a dominant majority, this article aims to unravel a nuanced power balance, where those in the minority perceive the dominant culture both as a threat to its way of life and as a despised entity, but paradoxically rely entirely on its financial support. This reveals a complex and intricate interplay of dominance and dependence, shaping a therapeutic relationship that defies conventional expectations.